The Implementation of Task Based Language Teaching (TBLT) Through Drama in Teaching Speaking - Hidayatin Fadhilah; Linta Wafdan Hidayah; Dinar Vincy Yunitaka Bahrudin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
English teacher should use appropriate teaching method to improve students’ speaking skill. Task based language teaching (TBLT) is the selected method of teaching speaking because TBLT focuses on language use in real contexts through the completion of relevant and meaningful task. In the use of task-based language teaching, the researcher uses drama. Drama is an appropriate choice in the implementation of TBLT because students are given the task practice of speaking and drama is suitable because in drama is dominant to be able to practice speaking from drama scripts. The researcher uses a case study. The researcher chooses at ninth grade of SMP Maarif 12 Pamekasan as the research subject because the students’ speaking skill is still low. The number of ninth grade students of SMP Maarif 12 Pamekasan consist of eight students. The results are the implementation of TBLT through drama is the pre task stage, the teacher introduced the topic and task of drama. During task stage, students work on the speaking drama performance in small groups, with the teacher monitoring the students. Then, the students perform their speaking drama in front of the class. The post task stage is the reflective stage, which the teacher guides the students to review and analyse the language that students have used in the task of drama. In the implementation of task based language teaching through drama, teacher and students face challenges. The teachers’ challenges are the activity needs a lot of time and differences in each student's speaking ability. On the other hand, the students’ challenges are cooperation in the group and insufficient practice time.